A highly specific rhodamine B based turn-on fluorescent probe for nitric oxide and application in living cells. Issue 46 (13th November 2020) - Liu, Yuanyuan; Jiao, Chunpeng; Wei, Yongchun; Lu, Wenjuan; Zhang, Pingping; Wang, Yanfeng
Abstract: The design and synthesis of two rhodamine derivatives with the same luminescent group, which have an interesting "turn-on" fluorescent response toward NO and can be readily prepared through one-step reaction in acetonitrile. Of the two compounds, rh-NO-1 showed high selectivity for NO among various reactive oxygen/nitrogen species, accompanied by a 24-fold fluorescent enhancement. With an increase of the amount of NO from 0 to 100 μM, the linear correlation between the fluorescent intensity of rh-NO-1 at 600 nm and the concentration of NO was found. The probe rh-NO-1 had good sensitivity and the detection limit was as low as 36.8 nM. Upon addition of NO, rh-NO-1 had a clear response within 2 min. This was a colour change from colorless to pink, which was visible to the naked eye. In addition, both rh-NO-1 and its derivative can be used to detect NO in living cells. Graphical abstract: Image 1 Highlights: A new rhodamine B probe was developed for NO using hydrazine hydrate or ethylenediamine as linker respectively. This probe shows "turn-on" fluorescent changes and is accompanied by a visible change from colorless to pink. This probe shows rapid response to NO, good sensitivity, highly selectivity and low cytotoxicity. This probe can be used to image NO in live cells.